Evaluation of fungal contamination and ochratoxin A detection in different types of coffee by HPLC‐based method. Issue 11 (15th September 2021) - Pakshir, Keyvan; Dehghani, Andishe; Nouraei, Hasti; Zareshahrabadi, Zahra; Zomorodian, Kamiar
Abstract: Background: Mycotoxins are secondary fungal metabolites that are produced by some toxigenic fungi on foodstuffs which are poisoning and potentiate for human's health hazards. In coffee samples, ochratoxin A and fungal contamination were examined. Methods: Immunoaffinity columns were used for treating of all 50 samples from four types of coffee, after that high‐performance liquid chromatography was used for determining the amount of ochratoxin. For the identification of fungi, all coffee samples were cultured in appropriated media. Results: The results showed that all samples were contaminated by ochratoxin A but only up to 50% of them had toxins higher than acceptable level as detected in black beans (47%), green beans (33.3%), torch (33.3%), and espresso (25%). Black coffee had a higher mean concentration of ochratoxin A than green coffee. Conclusion: Predominant fungi isolated from coffee samples were Aspergillus species. Finally, careful monitoring of mycotoxins in coffee samples is essential to improve the quality of this favorable beverage in future. Abstract : Different steps of ochratoxin A extraction from coffee.